1994
DOI: 10.1063/1.466295
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of the photodissociation and photodesorption of CD3I adsorbed on the TiO2(110) surface

Abstract: The ultraviolet photodissociation and photodesorption of CD3I adsorbed on the TiO2(110) surface at ∼100 K has been investigated at 257, 275, 302, and 351 nm using modulated continuous-wave laser irradiation followed by resonantly enhanced multiphoton ionization of fragments expelled from the adsorbate layer. Photodissociation at these wavelengths produces CD3 radicals. Nonthermal photodesorption also contributes to removal of CD3I from the adsorbate layer, becoming a major mechanism at 351 nm. Similar processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 62 publications
3
35
1
Order By: Relevance
“…This author observed the ejection of methyl radicals from the surface of R TiO 2 (110) during UHV photodecomposition of adsorbed acetone [701,752,753]. Similar observations have been made by Stair and coworkers for photodissociation of methyl iodide on this surface [680,754,755]. The methyl radicals emitted from adsorbed acetone were shown to further decompose on the chamber walls to yield formaldehyde.…”
Section: Direct Versus Indirect Eventssupporting
confidence: 66%
See 3 more Smart Citations
“…This author observed the ejection of methyl radicals from the surface of R TiO 2 (110) during UHV photodecomposition of adsorbed acetone [701,752,753]. Similar observations have been made by Stair and coworkers for photodissociation of methyl iodide on this surface [680,754,755]. The methyl radicals emitted from adsorbed acetone were shown to further decompose on the chamber walls to yield formaldehyde.…”
Section: Direct Versus Indirect Eventssupporting
confidence: 66%
“…An example of this is seen in the photochemistry of alkyl halides on R TiO 2 (110). Stair, Weitz and coworkers [680][681][682][683] have shown that bandgap excitation of TiO 2 leads to electron attachment to these adsorbed molecules, but does not result appreciable photodecomposition (as seen in the gas phase). Instead, rapid back-electron transfer to the surface occurs followed by photodesorption of the alkyl halide via the so-called Antoniewicz mechanism [684].…”
Section: Tio 2 Conduction Band To Electron Acceptormentioning
confidence: 94%
See 2 more Smart Citations
“…CH 3 I is chosen for thermal and photochemistry studies at adsorbate/surface interfaces due to the weak C-I bond and its high photosensitivity. The adsorption and reaction of methyl iodide on the TiO 2 (110) surface have been extensively studied by Kim et al [11][12][13][14] and Garrett et al 15,16 The complex desorption TPD spectra suggest the coexisting of several distinct coverage regimes. The dissociatively (< 5%) adsorbed I atoms remain chemisorbed at 220 K. For photochemistry, it was found that the photodesorption of CD 3 I follows the substrate mediated mechanism in the monolayer regime.…”
Section: Introductionmentioning
confidence: 99%